The effect of drying land on the character of corn (Zea mays) on lightness properties. Issue 1 (February 2021) - Hadipernata, M; Al-Baarri, A N; Somantri, M; Munarso, J; Rachmat, R; Rahayu, E; Pratiwi, A F; Setyadi, B; Mawarid, A A; Pangestika, W; Lestari, F P
Abstract: Corn is one of the most popular agricultural commodities in Indonesia. As a traditional farming system, the corn was then dried under the sun after harvesting resulting in the specific appearance. This research was aimed at determining the lightness in corn after the dry process using the oven. The corn after harvesting in 120 days was transferred to the laboratory and oven-dried at 38-43°C for 7 days. Based on the research conducted, the lightness of the corn experienced changing day by day and through the detection using lightness value, the decrease could be determined. The conclusion of this study was that the longer the drying caused the reduction in lightness of the corn.